International survey on skin patch test procedures, attitudes and interpretation. Issue 1 (December 2016) - Tanno, Luciana; Darlenski, Razvigor; Sánchez-Garcia, Silvia; Bonini, Matteo; Vereda, Andrea; Kolkhir, Pavel; Antolin-Amerigo, Dario; Dimov, Vesselin; Gallego-Corella, Claudia; Becerra, Juan; Diaz, Alexander; Linares, Virginia; et al.
Abstract Background Skin patch test is the gold standard method in diagnosing contact allergy. Although used for more than 100 years, the patch test procedure is performed with variability around the world. A number of factors can influence the test results, namely the quality of reagents used, the timing of the application, the patch test series (allergens/haptens) that have been used for testing, the appropriate interpretation of the skin reactions or the evaluation of the patient's benefit. Methods We performed an Internet –based survey with 38 questions covering the educational background of respondents, patch test methods and interpretation. The questionnaire was distributed among all representatives of national member societies of the World Allergy Organization (WAO), and the WAO Junior Members Group. Results One hundred sixty-nine completed surveys were received from 47 countries. The majority of participants had more than 5 years of clinical practice (61 %) and routinely carried out patch tests (70 %). Both allergists and dermatologists were responsible for carrying out the patch tests. We could observe the use of many different guidelines regardless the geographical distribution. The use of home-made preparations was indicated by 47 % of participants and 73 % of the respondents performed 2 or 3 readings. Most of the responders indicated having patients with adverse reactions, including erythroderma (12 %); however, only 30 % of members completed a consent form before conducting the patch test. Discussion The heterogeneity of patch test practices may be influenced by the level of awareness of clinical guidelines, different training backgrounds, accessibility to various types of devices, the patch test series (allergens/haptens) used for testing, type of clinical practice (public or private practice, clinical or research-based institution), infrastructure availability, financial/commercial implications and regulations among others. Conclusion There is a lack of a worldwide homogeneity of patch test procedures, and this raises concerns about the need for standardization and harmonization of this important diagnostic procedure.